1982
DOI: 10.2136/sssaj1982.03615995004600040023x
|View full text |Cite
|
Sign up to set email alerts
|

Field Vs. Laboratory Determined Hydraulic Conductivities of Some Slowly Permeable Horizons

Abstract: Saturated hydraulic conductivities K(µm/s) of soils of spodic and argillic horizons were measured in several Florida soils. The soils were Haplaquods, Haplohumods, Glossaqualfs, and Argiaquolls. Two methods of measurement were compared. The core method consistently gave larger hydraulic conductivity values than the piezometer method. The lowest K(µm/s) rates were in argillic horizons. The permeability classification of most soils studied depended upon the measurement method used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The study was conducted in a naturally regenerated P. taeda stand near Andalusia, AL, USA at the Solon Dixon Educational Center (31.1427°N, 86.6963°W) on a complex of two soil series, that is, Dothan sandy loam and Malbis fine sandy loam. These sandy loam soils contain an argillic horizon and are characterized by moderate to moderately low saturated hydraulic conductivities (Clapp & Hornberger, 1978;Rawls et al, 1998;Watts et al, 1982). The stand was approximately 5-7 years old at the onset of the experiment and contained young trees of Pinus echinata Mill.…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
“…The study was conducted in a naturally regenerated P. taeda stand near Andalusia, AL, USA at the Solon Dixon Educational Center (31.1427°N, 86.6963°W) on a complex of two soil series, that is, Dothan sandy loam and Malbis fine sandy loam. These sandy loam soils contain an argillic horizon and are characterized by moderate to moderately low saturated hydraulic conductivities (Clapp & Hornberger, 1978;Rawls et al, 1998;Watts et al, 1982). The stand was approximately 5-7 years old at the onset of the experiment and contained young trees of Pinus echinata Mill.…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
“…Variations in the soil texture within the same site is frequently observed. Several other studies have demonstrated that significant variation of hydraulic conductivity within a single soil mapping unit is common (Baker, 1978;Topp et al, 1980;Geohring, 1983;and Watts et al, 1982).…”
Section: Soil Texturementioning
confidence: 99%
“…Zobeck et al (1985) have shown that vertical K for soil with macropores varied from 20 to over 100 times that of soil without macropores. Taherian et al (1976) and Watts et al (1982) have reported that field measurement of K are subject to soil differences causing conductivity variations that may be larger than the difference between the methods.…”
Section: Mean Hydraulic Conductivity Values Determined With the Guelpmentioning
confidence: 99%